2009
DOI: 10.1136/bjo.2008.151720
|View full text |Cite
|
Sign up to set email alerts
|

Trachoma in the Pacific Islands: evidence from Trachoma Rapid Assessment

Abstract: The findings indicate that trachoma is present in all the Pacific Island countries screened. Further prevalence studies are required, and trachoma control measures should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 12 publications
(12 reference statements)
1
27
0
Order By: Relevance
“…More recently, trachoma rapid assessments (TRA) conducted in the Pacific indicated the presence of trachoma in Fiji, Vanuatu, Solomon Islands, Nauru and Kiribati. Although TRAs do not give accurate estimates of disease prevalence, the TRA data suggested that, whilst TF levels appeared high, both TI and TT were surprisingly scarce [10]. …”
Section: Introductionmentioning
confidence: 99%
“…More recently, trachoma rapid assessments (TRA) conducted in the Pacific indicated the presence of trachoma in Fiji, Vanuatu, Solomon Islands, Nauru and Kiribati. Although TRAs do not give accurate estimates of disease prevalence, the TRA data suggested that, whilst TF levels appeared high, both TI and TT were surprisingly scarce [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Other Western Pacific Island countries have also reported similar findings (unpublished data, Mr O. Sokana, Dr C. Macleod; personal correspondence, Ms F. Taleo). 14,23 Interestingly, in Aboriginal communities in nearby Australia, blindness from trachoma is still a public health issue. 16 We could hypothesize that different C. trachomatis strains from the ones associated elsewhere with trachoma could be found in the Pacific, perhaps with gene polymorphisms (such as in the matrix metalloproteinases) 24 that are important to the scarring process.…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern has been seen in other Western Pacific countries such as the Solomon Islands, Vanuatu, and Fiji, where recent surveys have found a high prevalence of TF in the children, but with little TT seen in adults (unpublished data, Mr O. Sokana; personal correspondence, Ms F. Taleo). 14 However, in neighboring Australia, trachoma is still a significant cause of blindness in remote Indigenous communities. A 2008 population-based survey found trachoma in 60% of such communities, with TT present in 1.4% of Indigenous adults examined.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, a trachoma rapid assessment was conducted in 17 sites in Tafea and Shefa province, indicating that trachoma was a likely to be significant public health burden [16]. A population-based prevalence survey was therefore required to determine the prevalence of TF in Vanuatu, to guide application of community-level interventions[17].…”
Section: Introductionmentioning
confidence: 99%